PELANGGARAN HAM BERAT PADA KONFLIK BERSENJATA DI SURIAH DITINJAU DARI HUKUM INTERNASIONAL - Jesaya Brahmana; Abdul Rahman; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2013)
Abstraction   Armed conflict in Syria is still in progress at the time this paper was written, and there are no signs of the conflict will cease. The conflict has been going on for more than two years and has caused many deaths and many who fled to Syria's neighboring countries such as Turkey, Lebanon, Jordan, and Iraq. Victims of the conflict are usually women and children. This journal suggests concerns about the forms of gross human rights violations under international law, the link between the fight against human rights violations, as well as the efforts of the UN and the international community.The method used in this paper is a literature study methods by collecting the materials or writing data from the print media, books, newspapers, law, magazines, editorial, and electronic media. Conclusions in this paper is that the severe human rights violations were categorized as a crime against the international and human rights. that there is a link between human rights violations in armed conflict or war. that there has been a lot of efforts in the United Nations and the international community to uphold human rights in Syria. However there has been no sign of armed conflict in Syria will stop because of disagreements among permanent members of the UN council